HEALTH REGULATION CHANGES IN INDONESIA: LEGAL AND POLICY REVIEW - Jackson Yumame; Henderina Morin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Changes in health regulations in Indonesia through Law No. 17 of 2023 mark an important transformation in the national legal and health policy system. This study aims to examine these regulatory changes in depth from a legal and policy perspective, highlighting the process, substance, and implications for the national health system. The research method used is normative legal analysis with a descriptive-analytical approach through a literature review of legislation, legal documents, and related literature. The findings indicate that the new regulations simplify and integrate previous laws, strengthen legal protection for healthcare workers and patients, and promote efficiency, transparency, and innovation in healthcare services. However, the implementation of these regulations still faces challenges such as harmonising derivative regulations, resistance from some stakeholders, and the need to strengthen resources and infrastructure. Overall, the changes in health regulations provide a more adaptive and comprehensive legal foundation, but the success of the reform depends heavily on the effectiveness of implementation and synergy among stakeholders.